2015
DOI: 10.1016/j.immuni.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Gut-Busters: IL-17 Ain’t Afraid of No IL-23

Abstract: Antibodies targeting IL-23 ameliorate clinical symptoms of inflammatory bowel disease. Paradoxically, IL-17 neutralization exacerbates colitis. In this issue, Lee et al. and Maxwell et al. reveal a protective function of IL-17 through maintenance of intestinal barrier integrity, helping to explain this dichotomy (Lee et al., 2015; Maxwell et al., 2015).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 12 publications
1
39
0
2
Order By: Relevance
“…IL-23 inhibition had attenuated CD as well as promoting the development of the regulatory T cells (40). In another study, antibodies targeting IL-23 had ameliorated colitis (41). Results of this study are consistent with these observations because both IL-17A and IL-23 appear to perform dual roles in colitis.…”
Section: Thesupporting
confidence: 82%
“…IL-23 inhibition had attenuated CD as well as promoting the development of the regulatory T cells (40). In another study, antibodies targeting IL-23 had ameliorated colitis (41). Results of this study are consistent with these observations because both IL-17A and IL-23 appear to perform dual roles in colitis.…”
Section: Thesupporting
confidence: 82%
“…We next confirmed that human OECs stimulated with IL-17 induced secretion of BD2, the human orthologue of murine BD3 (Fig 6D). Since clinical blockade of IL-17 is associated with impaired epithelial repair in the gut (Whibley and Gaffen, 2015), we asked whether IL-17 can protect from cell damage induced by C. albicans . However, IL-17 did not alter the cytotoxicity arising from C. albicans infection of cultured OECs, measured by secretion of lactate dehydrogenase (Fig 6E).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the intestinal epithelium damage caused by the IBD state is thought to trigger higher levels of FGF-2, a propagator of ISC regeneration, which works with IL-17Ato promote mucosal healing and intestinal epithelial cell proliferation (Brockmann et al, 2017; Houchen et al, 1999). Also, in clinical trials and studies with colitis mouse models, anti-IL-17A treatments aggravate IBD-associated symptoms, suggesting that IL-17A may play a role in reducing intestinal inflammation and promote gut healing (Whibley and Gaffen, 2015). TNFα has been previously reported to be chronically elevated in IBD patients, and TNFα inhibitors, such as infliximab and adalimumab, have long been established as effective treatments for IBD patients (Lichtenstein, 2013).…”
Section: Discussionmentioning
confidence: 99%